Estudio de la calidad de la leche de cabra "Chusca Lojana" en Yamana y El Limón del cantón Paltas - Pineda Carabali, Priscila Alexandra (2019)
In the dry forest area of Canton Paltas, because of most of population is dedicated to goat production as the main source of economic income; was carried out an investigation where the production levels and milk quality were determined through physical-chemical analysis, according the biotype, lactation stage, number of births, place of origin of the goat milk produced as in the Yamana parish as El Limon neighborhood from Canton Paltas. Were used 42 "Chuscas" goats which were in different numbers of births and stages of lactation; The analysis was carried out in 6 goat herds with 4 visits and 4 repetitions to have a greater degree of reliability. The samples were analyzed at the "Dairy Products Pilot Plant of the National University of Loja". Obtaining the following values: Milk production of the “Chusca” goat is 37170 ml in 150 days of lactation, with a daily average of 247.8 ml. In Yamana 292 ml, Limon 301 ml. Production according to births; First birth 226 ml, second birth 325 ml, third birth 364 ml, fourth birth 327 ml, fifth birth 242 ml, 3 breastfeeding peaks at days 40, 110 and 130 with 290 ml, 309 ml and 470 ml respectively. Through the physical chemical analysis were obtained: Fat (6.58%), non-fatty solids (8.10%), total solids (15.2%), density (1.026 g / ml), lactose (4.46%), mineral sales (0.67%), protein (2.98%), pH (6.79), conductivity (4.89 ms / cm). The quality of milk is influenced according to the place, demonstrating values slightly raised in the goats milk from the Yamana sector compared to those from El Limón. It is recommended to administer nutritional supplements and improve the management of goats. Keywords: Goat "Chusca Lojana", goat milk, milk quality, duration of breastfeeding, number of births.